Information sharing, credit booms, and financial stability - Samuel Guérineau; Florian Léon (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
This paper analyzes the impact of credit information sharing on financial stability, drawing special attention to its interactions with credit booms. A probit estimation of financial vulnerability episodes – identified by jumps of the ratio of non-performing loans to total loans, is run for a sample of 159 countries dividing in two sub-samples according to their level of development: 80 advanced or emerging economies and 79 less developed countries. The results show that: i) credit information sharing reduces financial fragility for both groups of countries; ii) for less developed countries, the main effect is the direct effect (reduction of NPL ratio once credit boom is controlled), suggesting a portfolio quality effect; iii) for advanced and emerging countries, credit information sharing (IS) also mitigates the detrimental impact of credit boom on financial fragility, iv) the depth of IS has an negative impact on the likelihood of credit booms (but not the coverage of IS).Keywords: Information sharing, financial stability, credit booms
Keywords: G21; G28; 330; Information sharing; Financial Stability; credit booms